ANALISIS TITIK IMPAS USAHA PEMBUATAN IKAN KERING DI KOTA BENGKULU - Melysa Nabilasari; Nola Windirah; Bambang Sumantri (BPFP Faperta UNIB, 2022)
Dried fish business is a household business of processing fresh fish which is often found in the coastal areas of Bengkulu City, including in Sumber Jaya Village. This effort has been done for years by local residents. In the initial survey of the research, it was found that the makers of dried fish in that location only produce without any planning. Sales and expenses are allowed to flow as they are without proper calculations and records. To overcome this business strategic planning, it can be done by calculating the break even point (BEP). The break-even point is the point at which the total costs and revenues are the same, meaning that the business neither loses nor gains. The purpose of this study was to determine the break-even point of dried fish business in Bengkulu City. This research was carried out for approximately 1 month by taking 47 dried fish makers. This sampling process is conducted by simple random sampling. The results showed that the dried fish business in Bengkulu City had already exceeded its break-even point and was feasible to operate or run. The value of the break-even point of dry fish production is 2.45 kg, equivalent to fresh half dried fish beledang in one processing, the break-even point of revenue is Rp 104,022.08, and the break-even point price is Rp 30,508.96 per kg.